Wittgenstien's lectures : Cambridge 1930-1932 / edited by Desmond Lee - "Lee,Desmond (ed.)" (Oxford, 1980)
This book is particularly interesting in that it records the first series of lectures and discussions held by Wittgenstein after his return to Cambridge in 1929. From then until his death in 1951 he influences philosophy almost exclusively through teaching and discussion, and though copies of The Blue and Brown Books circulated in manuscript during his lifetime he never brought any of his writings to a form in which he was prepared to publish them.
Keywords: "Philosophy- adresses, essays, lectures"